Development of portable solar generator - Mat Jamil, Khamelrun Shah (2015)
The increase of demand for energy, stimulated by developing countries and consequent decrease of power sources, is leading to an unsustainable future. These way renewable and clean energies are necessary to be used, particularly solar energy. It can produce heat or be directly converted into electricity, called photovoltaic (PV) energy. JX Crystals Inc is developing a class of compact portable solar generators using commercially available 32% efficient multifunction solar cells. Three different sized solar generators with nominal power ratings of 12 W, 36 W and 75 W are described. The high solar cell efficiency will allow all three units to be small, portable, and light weight. (For example, the 12 W generator will fit in a pocket.) The 36 W Charger is exemplary. The 36 W Charger in its stowed form will resemble a notebook computer case in size and form Deployed, its physical size is half that required for a traditional Silicon 16% solar cell Charger and one-quarter that for a 8% thin film solar cell Charger. A challenge for the use of these 32% efficient cells is their cost. This cost can be reduced ten fold through the use of linear Fresnel lenses as per the designs described herein. The challenge is to preserve simplicity of operation. By using bypass diodes in the cell circuits and by orienting the lens focal line and cell circuit East and West, the smaller 12 W and 36 W units can be easily aimed at the sun and they will then maintain output without adjustment for 2 hours in the middle of a sunny day. A simple 1-axis solar tracker is also proposed for the larger 75 W unit. It can fit within the stowed case where the case will fit within a backpack.